1993
DOI: 10.1002/ajh.2830430111
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia associated with bone marrow fibrosis: Possible role of interleukin 1α in the pathogenesis

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) associated with bone marrow fibrosis is described. The conditioned medium of the CLL cells contained a high quantity of interleukin 1 alpha (IL-1 alpha), and showed growth promoting activity for marrow fibroblasts which was partially inhibited by anti IL-1 alpha antibody. In addition, the conditioned medium as well as IL-1 alpha stimulated the growth of marrow fibroblasts from the patient. These results strongly suggested the marrow fibrosis occurred by the secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…However, it induces HSC proliferation (18) and expression of intercellular adhesion molecule-1 and chemokines in a nuclear factor-B-dependent manner (17,19). Although insufficiently documented for HSC activation, IL-1 is accepted as a potent cytokine for fibrosis of other organs such as the lung, (20) bone marrow (21), and kidney (22,23).…”
mentioning
confidence: 99%
“…However, it induces HSC proliferation (18) and expression of intercellular adhesion molecule-1 and chemokines in a nuclear factor-B-dependent manner (17,19). Although insufficiently documented for HSC activation, IL-1 is accepted as a potent cytokine for fibrosis of other organs such as the lung, (20) bone marrow (21), and kidney (22,23).…”
mentioning
confidence: 99%
“…The simultaneous occurrence of lymphoproliferative and myeloproliferative disorder is very rare [1–4]. It is still under investigation whether these two clonal disorders are caused by one primary genetic alteration that increased genomic instability and susceptibility to further clonal disorders or are purely coincidental findings of a different origin [58]. …”
Section: Introductionmentioning
confidence: 99%
“…Secondary myelofibrosis occurs in 20-30% of CLL cases, but usually does not manifest clinically [3]. Kimura et al have suggested that the marrow fibrosis occurs by the secretion of IL-1 alpha from the CLL cells causing growth stimulation of marrow fibroblasts [1]. A review of literature revealed anecdotal case reports of coexistent CLL with myelofibrosis [4].…”
mentioning
confidence: 99%
“…Coexistence chronic lymphocytic leukemia (CLL) with myelofibrosis is a rare association, though CLL has been described to occur with solid tumors [1][2][3]. When these two coexist, either CLL may precede or follow idiopathic myelofibrosis [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation